Oil and gas company policy regarding the concept of sustainable development (water resources); IOP Conference Series: Earth and Environmental Science; Vol. 33 : Contemporary Issues of Hydrogeology, Engineering Geology and Hydrogeoecology in Eurasia - Matyugina E. G. Eleonora Grigorievna; Pozharnitskaya O. V. Olga Vyacheslavovna; Grinkevich L. S.; Belozerova D. S.; Strelnikova A. B. Anna Borisovna (Natural Waters Resources, 2016)
Title screen